Răspuns :
a) 3x + 2 = -7
3x=-7-2
3x=-9
x=-9/3
x=-3
b) 5x - 4 = -14
5x=-14+4
5x=-10
x=-10/5
x=-2
c) 2x + 35 = 15
2x=15-35
2x=-20
x=-20/2
x=-10
d) 7x + 14 = 0
7x=-14
x=-14/7
x=-2
e) -2x + 3 = -7
-2x=-7-3
-2x=-10 ·-1
2z=10
z=10/2
z=5
f) -3x + 5 = -10
-3x=-10-15
-3x=-15 ·-1
3x=15
x=15/3
x=5
g) -5x + 5 = 5
-5x=5-5
x=0
2. Rezolvati in Z ecuatiile :
a) 2x + 12 = x + 4
2x-x=4-12
x=-8
b) 2x + 23 = x - 9
2x-x=-9-23
x=-32
c) 3x - 4 = x + 11
3x-x=11+4
2x=15
x=15/2
d) 4x + 8 = 3x + 29
4x-3x=29-8
x=21
e) 2x - 7 = -x +5
2x+x=5+7
3x=12
x=12/3.
x=4
f) 4x - 32 = x + 4
4x-x=4+32
3x=36
x=36/3
x=12
g) 2x + 34 = 16 + x
2x-x=16-34
x=-18
h) 6 - 3x = x + 14
-3x-x=14-6
-4x=8 ·-1
4x=-8
x=-8/4
x=-2
i) -x + 9 = x + 31
-x-x=31-9
-2x=22 ·-1
2x=-22
x=-22/2
x=-11
j) 8 - 2x = -x +12
-2x+x=12-8
-x=4 ·-1
x=-4
k) 4 + 3x = -68 + x
3x-x=-68+4
2x=-64
x=-64/2
x=-32
l) 2 + 9x = -78 -x
9x+x=-78-2
10x=-80
x=-80/10
x=-8
3x=-7-2
3x=-9
x=-9/3
x=-3
b) 5x - 4 = -14
5x=-14+4
5x=-10
x=-10/5
x=-2
c) 2x + 35 = 15
2x=15-35
2x=-20
x=-20/2
x=-10
d) 7x + 14 = 0
7x=-14
x=-14/7
x=-2
e) -2x + 3 = -7
-2x=-7-3
-2x=-10 ·-1
2z=10
z=10/2
z=5
f) -3x + 5 = -10
-3x=-10-15
-3x=-15 ·-1
3x=15
x=15/3
x=5
g) -5x + 5 = 5
-5x=5-5
x=0
2. Rezolvati in Z ecuatiile :
a) 2x + 12 = x + 4
2x-x=4-12
x=-8
b) 2x + 23 = x - 9
2x-x=-9-23
x=-32
c) 3x - 4 = x + 11
3x-x=11+4
2x=15
x=15/2
d) 4x + 8 = 3x + 29
4x-3x=29-8
x=21
e) 2x - 7 = -x +5
2x+x=5+7
3x=12
x=12/3.
x=4
f) 4x - 32 = x + 4
4x-x=4+32
3x=36
x=36/3
x=12
g) 2x + 34 = 16 + x
2x-x=16-34
x=-18
h) 6 - 3x = x + 14
-3x-x=14-6
-4x=8 ·-1
4x=-8
x=-8/4
x=-2
i) -x + 9 = x + 31
-x-x=31-9
-2x=22 ·-1
2x=-22
x=-22/2
x=-11
j) 8 - 2x = -x +12
-2x+x=12-8
-x=4 ·-1
x=-4
k) 4 + 3x = -68 + x
3x-x=-68+4
2x=-64
x=-64/2
x=-32
l) 2 + 9x = -78 -x
9x+x=-78-2
10x=-80
x=-80/10
x=-8